Lipid biomarker and bulk organic matter concentrations and carbon and hydrogen isotope data from sediment cores GeoB7805-1 and GeoB7807-2 - Christoph Häggi; Jürgen Pätzold; Steven Bouillon; Enno Schefuß (PANGAEA, 2020)
The data set contains lipid biomarker and bulk organic matter data from two sediment cores in the Shaban Deep, in the northern Red Sea. One core is deposited in the hypersaline brine (GeoB7805-1 2) and the other core (GeoB7807-2) is deposited outside the brine. The data set compares the lipid biomarker signals in the two deposition settings. For both cores the data set contains total organic carbon data, total nitrogen data, bulk organic matter carbon and hydrogen isotope data, long-chain n-alkane concentrations, alkenone concentrations, long- and short-chain fatty acid concentrations, long-chain n-alkane and long-chain fatty acid average chain length and carbon preference index data, UK37 data, stable carbon and hydrogen isotope data for long-chain n-alkanes, alkenones, and long- and short chain fatty acids.